2018
DOI: 10.1148/radiol.2018172886
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of Endovascular Therapy for Acute Ischemic Stroke: A Systematic Review of the Impact of Patient Age

Abstract: Purpose To determine the impact of patient age on the cost-effectiveness of endovascular therapy (EVT) in addition to standard care (SC) in large-vessel-occlusion stroke for patients aged 50 to 100 years in the United States. Materials and Methods A decision-analytic Markov model was used to estimate direct and indirect lifetime costs and quality-adjusted life years (QALYs). Age-dependent input parameters were obtained from the literature. Deterministic and probabilistic sensitivity analysis for age at index s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 56 publications
2
30
0
Order By: Relevance
“…Importantly, this implies that the costs for long-term care will also be reduced. At $20,837/QALY, the advanced CTAP imaging strategy should be considered appropriate for adoption in clinical care when considering a threshold of $50,000/QALY, which is customarily used as a threshold in health policy (4,5,17,25,34). Furthermore, our model results, based on Medicare CPT reimbursement, showed that for diagnostic imaging, the advanced CTAP imaging strategy is more costly than the standard-of-care strategy.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Importantly, this implies that the costs for long-term care will also be reduced. At $20,837/QALY, the advanced CTAP imaging strategy should be considered appropriate for adoption in clinical care when considering a threshold of $50,000/QALY, which is customarily used as a threshold in health policy (4,5,17,25,34). Furthermore, our model results, based on Medicare CPT reimbursement, showed that for diagnostic imaging, the advanced CTAP imaging strategy is more costly than the standard-of-care strategy.…”
Section: Discussionmentioning
confidence: 88%
“…The ongoing operational and clinical acute care costs were derived from the published literature as shown in Table 2, which utilize Medicare CPT codes to estimate the costs. It is standard practice in health economics evaluations to use Medicare reimbursement as a substitute for actual costs (25,33,34) to minimize bias from practice variation. These costs include depreciation on all depreciable type assets that are used to provide covered services to beneficiaries (35).…”
Section: Methodsmentioning
confidence: 99%
“…Our study adds to the field as it demonstrated the costeffectiveness of supplemental short-protocol MRI subsequent to negative head CT in neurological emergency patients. In many related fields of research, the additional utilization of procedures and diagnostic tests has been shown to be cost-effective: Despite high costs in the acute setting, interventional treatment has been shown to be cost-effective in major stroke patients, even in patients with a limited overall life expectancy [26,36]. Furthermore, a transition from a time window to a tissue window for stroke patients presenting with unknown onset time for endovascular treatment and intravenous thrombolysis has taken place [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…19,20,25,26 In higher-income countries in Europe and North America, endovascular therapy have been found to be ''cost-effective'' using contemporary willingness-to-pay threshold for qualityadjusted life year (QALY) gained for patients up to 100 years old, and even cost-saving from a societal perspective for patients up to 79 years old. 27 Whether the same cost-utility analyses remain favorable in middle-or low-income countries is yet to be determined. Equitable access to thrombectomy service is another concern in these countries where income disparity may be significant and comprehensive public health care coverage lacking.…”
Section: Discussionmentioning
confidence: 99%